Arsitektur sebagai relasi doing and being - Reginaldo Chistophori Lake (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2020)
ARTEKS : Jurnal Teknik Arsitektur, volume 5, issue 3, December 2020 presents the fifteen on the conception of research results, which defined architecture as an inseparable coin related to